Preparation method and application of polyvinylidene fluoride resin
By adding specific additives to the polymerization reaction and controlling the reaction conditions, the PVDF resin with high β phase content was prepared by suspended polymerization, which solved the problem of low β crystal form content of PVDF materials in the prior art, and achieved an efficient and simplified preparation process and excellent piezoelectric properties.
Patent Information
- Application Number
- CN202510000734.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art is difficult to effectively increase the β crystal content in polyvinylidene fluoride (PVDF) materials, resulting in poor piezoelectric performance, and the preparation process is complicated and difficult to industrialize.
By adding water, chain transfer agent, initiator, nanoparticles and dispersant to the polymerization reaction, the two-stage reaction was carried out by suspended polymerization method, the reaction temperature and pressure were controlled, and the β-crystal phase was induced by nanometal oxides. Finally, the nanoparticles were removed by pickling to obtain a PVDF resin with a high β-phase content.
The preparation of PVDF resin with high β crystal form content has been achieved, which improves its piezoelectric properties, simplifies the preparation process, reduces the width of impurity content and molecular weight distribution, and is suitable for the application of piezoelectric materials in industrial automation, medical equipment and other fields.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymers, and in particular to a preparation method of polyvinylidene fluoride resin and application thereof. Background Art
[0002] With the rapid development of flexible wearable electronic products and the increasing demand in medical health, human movement and military fields, flexible sensors, as key components for obtaining human physiological signals and movement, have become a research hotspot. Wearable electronic products have received more and more attention, and piezoelectric materials can convert mechanical energy into electrical energy, and have potential application prospects in energy harvesting, sensors, etc. Polyvinylidene fluoride (PVDF) is one of the most attractive candidate materials for energy harvesting applications among polymer piezoelectric materials. It has a high piezoelectric coefficient, excellent stability and ideal sensitivity, which promotes its application in different fields.
[0003] PVDF is a chain-like semi-crystalline polymer formed by monomers, which has both crystalline and amorphous regions inside. So far, the five crystal forms of α, β, γ, δ, and ε have been discovered in large numbers. Among them, the β-crystal molecular chain is arranged in an all-trans conformation, showing good piezoelectricity. Therefore, increasing the content of β-crystal can greatly improve the piezoelectric properties of PVDF materials. At present, many methods have been proven to be able to increase the β-phase content, such as mechanical stretching from the melt, high pressure, high electric field polarization, melt-induced crystallization, and quenching, but these methods are complicated and the β-crystal content obtained is low. Therefore, it is of great significance to study new preparation methods for PVDF with high β-phase content.
[0004] Patent CN117229526A discloses a method for preparing high-crystallinity β-PVDF, wherein PVDF particles are stirred and dissolved in DMF to prepare a PVDF / DMF solution, the PVDF / DMF solution is poured onto a clean glass sheet and dried to obtain a PVDF membrane, a nucleating agent aqueous solution is dripped onto the surface of the PVDF membrane to obtain a PVDF membrane coated with a nucleating agent; the PVDF membrane coated with a nucleating agent is melted and quenched, and the nucleating agent is washed off to obtain β-phase PVDF. However, this method still has many steps and is not easy to industrialize, and the nucleating agent hexadecyltrimethylammonium bromide used is toxic and not easy to be washed away.
[0005] Patent CN114106373A discloses a method for preparing a PVDF film with a high β-crystal content, using ordinary PVDF pellets as raw materials, hot pressing and γ-ray irradiation cross-linking to prepare a cross-linked prefabricated film; then melt stretching is performed, and a large amount of β-crystals are induced to directly generate in the PVDF melt by regulating the temperature field and the stretching flow field. Although the PVDF film obtained has a high β-crystal ratio, it needs to go through molding, γ-ray irradiation, melt stretching, heat preservation and curing processes from the PVDF raw materials. The steps are cumbersome and γ-ray radiation is harmful to the human body. In addition, the β-crystal content in the material obtained by mechanical stretching is seriously dependent on the conditions during stretching, and the preparation conditions need to be strictly controlled during the stretching process.
[0006] Patent CN109762188A discloses a method for continuously preparing PVDF with high β-crystal content by melt extrusion-rolling, using ordinary PVDF pellets as raw materials, and applying mechanical force during the rolling process to transform the configuration of PVDF molecules from α-crystal to β-crystal. Although the preparation process is non-toxic, pollution-free and low-cost, the invention uses a micro twin-screw extruder and a small mold, which can only be used in laboratory tests, and the thickness of the high β-crystal PVDF film cannot be accurately controlled, and the performance of the film is easily damaged during the mechanical extrusion process.
[0007] The above-mentioned methods for preparing PVDF with high β-crystal content are all post-production processing and preparation methods, and most of them are mechanical stretching to prepare films. However, the PVDF film obtained has a low yield, many holes and is fragile. The β-crystal content in the material obtained by mechanical stretching is seriously dependent on the conditions during stretching, and the preparation conditions need to be strictly controlled. There are also literatures that use solution casting, mechanical stretching, electric field polarization and other methods to obtain the β phase of PVDF, but the preparation process is cumbersome and additives will be added during the process to affect the purity of PVDF. At present, the technology for improving the β phase of PVDF from the polymerization process is rare.
[0008] In summary, how to create a new preparation method for PVDF with high β-phase content is of great significance. Summary of the invention
[0009] In order to solve the above problems, the present invention provides a preparation method of polyvinylidene fluoride resin with high β-phase content and application thereof.
[0010] To achieve the above object, the present invention provides the following technical solutions:
[0011] A method for preparing a polyvinylidene fluoride resin comprises the following steps:
[0012] (1) adding water, chain transfer agent, initiator, nanoparticles and dispersant into a reaction kettle;
[0013] (2) adding vinylidene fluoride monomer as a base under stirring conditions, and then performing a polymerization reaction;
[0014] (3) After the polymerization is completed, unreacted monomers are removed and post-processed to obtain polyvinylidene fluoride resin.
[0015] In the present invention, the resistivity of the water in step (1) is above 18.3 MΩ·cm at 25° C., and the amount added is 100%-160% of the mass of the vinylidene fluoride monomer used as the base, preferably 110-150%.
[0016] The chain transfer agent in step (1) is an ester, preferably a carboxylate or a carbonate, more preferably one or more of ethyl acetate, dipropyl malonate, diethyl succinate, dipropyl succinate, diethyl malonate, diisopropyl carbonate, dimethyl carbonate, diethyl carbonate, ethylene carbonate, etc., and the amount of the chain transfer agent added is 0.3 to 3 wt% of the mass of the vinylidene fluoride monomer used as the base.
[0017] Preferably, the nanoparticles are nano metal oxides or hydroxides, which generally need to be ultrasonically dispersed in a certain amount of water for more than 30 minutes in advance, and the amount of water used for dispersion is 50-100 times the mass of the nanoparticles, preferably 60-70 times. The amount of nanoparticles used is 0.03-0.5% of the mass of the vinylidene fluoride monomer used as the base. The nano metal oxide / oxide or hydroxide not only plays a role in inducing the formation of β crystal phase in the suspension polymerization system, but also plays a role as a dispersant to stabilize the polymerization reaction system and prevent the droplets from agglomerating to form large particles.
[0018] In the present invention, the nano metal oxides or hydroxides are preferably alkaline earth metal or transition metal oxides or hydroxides, and more preferably metal oxides or hydroxides of zinc, aluminum, magnesium, titanium, zirconium, etc.
[0019] The nanoparticles in the present invention include but are not limited to one or a combination of two or more of nano zinc oxide, nano aluminum oxide, nano magnesium oxide, nano zinc hydroxide, nano aluminum hydroxide, nano magnesium hydroxide, nano titanium oxide, nano zirconium oxide, etc.;
[0020] In the present invention, the particle size of the nanoparticles is 10-500 nm, preferably 10-100 nm.
[0021] The dispersant in step (1) is a conventional dispersant for polymerization, such as one or a combination of two or more of polyethylene glycol, methyl cellulose, ethyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, and hydroxyethyl methyl cellulose.
[0022] Preferably, the amount of the dispersant used is 0.01 to 0.3% of the mass of the vinylidene fluoride monomer used as the base.
[0023] In the present invention, after the bottoming raw materials are added to the polymerization reactor, an oxygen removal operation is required, and nitrogen replacement is performed multiple times (at least 3 times) under a negative pressure environment to deoxygenate, and the final oxygen content is controlled below 20 ppm.
[0024] In order to improve the heat transfer and mass transfer effect of the polymerization reaction in the present invention, especially to ensure that the substances in the system can be fully mixed and uniform, the stirring during the reaction process adopts an axial flow blade, the reactor is a high-pressure vertical reactor or a high-pressure spherical reactor, the aspect ratio of the reactor should be less than 1.5, the ratio of the blade diameter to the inner diameter of the reactor should be greater than 0.5, and the rotation speed during the reaction process is 450rpm-650rpm, preferably 550rpm.
[0025] In the present invention, the polymerization reaction temperature is 40-75° C. and the pressure is 7-14 MPa.
[0026] Preferably, the polymerization reaction is carried out in two stages.
[0027] Preferably, the temperature of the first stage of suspension polymerization is 40-50° C., preferably 45° C., and the temperature of the second stage is 60-75° C., preferably 70° C. It should be noted that if the reaction temperature is too high, the decomposition half-life of the initiator will decrease rapidly, the content of active free radicals will increase, the reaction rate will increase sharply, the heat release will also increase sharply, and over-temperature implosion will easily occur, resulting in over-temperature and over-pressure of the reactor.
[0028] In the present invention, the reaction pressure is 7-14Mpa, and the reaction pressure is controlled by the amount of vinylidene fluoride introduced during the reaction. The vinylidene fluoride monomer of the present invention adopts a continuous feeding method. Before the reaction starts, a certain amount of vinylidene fluoride is first introduced as a bottom, and during the reaction, the vinylidene fluoride monomer is continuously introduced into the system, and the reaction pressure is maintained at 7-14Mpa.
[0029] In the present invention, the initiator is a peroxide initiator or an azo initiator, preferably one or more of dibenzoyl peroxide, dilauroyl peroxide, azobisisobutyronitrile, azobisisoheptanenitrile, tert-butyl peroxyisopropylformate, and diethylhexyl peroxydicarbonate.
[0030] Preferably, the amount of the initiator added is 0.1-0.5 wt % of the mass of the vinylidene fluoride monomer used as the base.
[0031] Preferably, the initiator is added in multiple times. Before the polymerization reaction starts, a portion of the initiator is added as a base (accounting for 10-20% of the total initiator amount), and then the initiator is added in multiple times. If the reaction rate begins to decrease, the initiator is added in 2-4 times (the interval time and the amount added each time are adjusted according to the actual reaction situation). The addition of the initiator in multiple times can effectively control the reaction rate and is beneficial to the nucleation and crystallization of PVDF.
[0032] In the present invention, the post-treatment after the reaction includes mother liquor slurry filtration, acid washing, pure water washing, filter pressing, drying, etc., which can be carried out by methods known in the art and are not required here.
[0033] Preferably, after the mother liquor slurry is filtered, water is added to the filtered filter cake for stirring and dispersion, and the amount of water added is 5-20 times the weight of the wet material, preferably 10 times, and then the slurry is filter pressed, wherein most of the nanoparticles can be removed, and then the material is stirred and washed with an acid solution for at least 30 minutes, wherein the types of acids include but are not limited to sulfuric acid, hydrochloric acid, nitric acid, acetic acid, etc., and the amount of acid added is 105-150 mol%, preferably 110 mol% of the nanoparticles; after acid washing, continue to use water for washing and filtering until the conductivity of the filtrate is less than 2μS / cm.
[0034] The present invention also provides application of the polyvinylidene fluoride resin prepared by the preparation method, which is used for piezoelectric materials.
[0035] The present invention has the following beneficial effects:
[0036] Usually, the surface of particles generally carries an electric charge, and a double electric layer is formed on the surface when dispersed in water. This surface effect is particularly evident in nano-metal oxides. The inventors have found in their research that adding nano-metal oxides or hydroxides to the polymerization system can induce the PVDF molecular chain to form a polar β-crystalline phase. The relative rates of crystal nucleation and growth are regulated by a two-stage reaction. The synthesized PVDF has high crystallinity and high β-crystalline phase content. At the same time, the added nano-oxides / hydroxides can be completely removed by low-concentration acid washing, and the final impurity content of the product is low and the molecular weight distribution is narrow.
[0037] The polyvinylidene fluoride obtained by the method of the present invention is particularly suitable for being used as a piezoelectric polymer in the fields of industrial automation, instrumentation, medical equipment, explosion shock measurement, etc. DETAILED DESCRIPTION
[0038] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the invention belongs. The term "and / or" as may be used herein includes any and all combinations of one or more of the associated listed items.
[0040] Main raw material sources
[0041] The main raw material information is as follows:
[0042] Vinylidene fluoride: Wanhua Chemical Group Co., Ltd., industrial products;
[0043] Ethyl acetate: AR, 99.5%, Beijing Inokai Technology Co., Ltd.
[0044] Ultrapure water: prepared by pure water machine, 18.3MΩ·cm or above
[0045] Diethylhexyl peroxydicarbonate: Zibo Zhenghua Auxiliary Agent, 40%
[0046] Polyethylene glycol: AR Beijing Inokai Technology Co., Ltd.
[0047] Nano zinc oxide: 50nm Beijing Inokai Technology Co., Ltd. 99.9%
[0048] Alumina: 20nm Beijing Inokai Technology Co., Ltd. 99.99%
[0049] Magnesium oxide: 50nm Beijing Inokai Technology Co., Ltd. 99.99%
[0050] Nano titanium dioxide: 30nm Anatase Beijing Inokai Technology Co., Ltd. 99.9%
[0051] Zirconia: 30nm Nanjing Tianxing New Materials Co., Ltd. 99.99%
[0052] Zinc hydroxide: 150nm Aike reagent AR
[0053] Magnesium hydroxide: 200nm Hubei Xinyuhong Biomedical Technology Co., Ltd. 98.5%
[0054] Aluminum hydroxide: 50nm Zhejiang Zhitai Nano Micro New Materials 99.9%
[0055] Main test methods
[0056] Crystallinity:
[0057] The test was carried out using a METTLER DSC-1 differential scanning calorimeter.
[0058] Relative content of β crystal:
[0059] The relative content of β crystal in PVDF is calculated by FTIR infrared absorption spectrum, where the infrared characteristic absorption peak of α crystal is located at 763cm-1, and the infrared characteristic absorption peak of β crystal is located at 840cm-1. The relative content calculation formula of β crystal is fβ=Aβ / (1.26Aα+Aβ)×100%, where Aβ and Aβ are the integral areas of characteristic absorption peaks of α crystal and β crystal respectively.
[0060] Molecular weight and its distribution
[0061] The molecular weight and distribution of the polymers were determined using Shimadzu gel permeation chromatography (GPC).
[0062] The resistivity of the ultrapure water used in the specific embodiment of the present application is above 18.3 MΩ·cm at 25°C.
[0063] In the specific implementation manner of the present application, the dispersion of nanoparticles is obtained by adding the nanoparticles into water and then performing ultrasonic dispersion for 40-60 minutes.
[0064] Example 1
[0065] In a 5-liter autoclave, 1950 g of ultrapure water, a pre-prepared nano zinc oxide (1.5 g) / water (90 g) dispersion, 0.6 g of diethylhexyl peroxydicarbonate initiator, 30 g of ethyl acetate chain transfer agent, and 0.5 g of polyethylene glycol dispersant were added. Nitrogen was introduced into the system under negative pressure for 5 times to control the oxygen content of the system below 20 ppm. Then, the stirring speed was set to 600 rpm, 1500 g of vinylidene fluoride monomer was added to the reactor, and the reactor temperature was raised to 44°C. After the reaction started, vinylidene fluoride monomer was continuously added to maintain the system pressure at 7.5 MPa. After 1.5 h of reaction, the reactor temperature was raised to 70°C for reaction. The remaining initiator diethylhexyl peroxydicarbonate (2.4 g) was added into the reactor three times (with an interval of 20 min), and vinylidene fluoride monomer was continuously added to maintain the system pressure at 12.5 MPa. After the reaction, the unreacted vinylidene fluoride monomer was removed, and the slurry product was transferred to a receiving tank through the lower expansion valve. After filtering the mother liquor, 15 L of ultrapure water was added to the filter cake, and the mixture was stirred evenly and then filtered. The product was then washed with sulfuric acid (1.987 g) / water (5 L). After continuous stirring and dispersing washing for 30 min, the above washing operation was performed with pure water until the final filtrate conductivity was less than 2 μS / cm. The sample was then dried at 80°C for 10 h.
[0066] Example 2
[0067] In a 5-liter autoclave, 1950 g of ultrapure water, a pre-prepared nano zinc oxide (0.45 g) / water (27 g) dispersion, 0.3 g of diethylhexyl peroxydicarbonate initiator, 4.5 g of ethyl acetate chain transfer agent, and 0.15 g of polyethylene glycol dispersant were added. Nitrogen was introduced into the system under negative pressure for 5 times to control the oxygen content of the system below 20 ppm. Then, the stirring speed was set to 450 rpm, 1500 g of vinylidene fluoride monomer was added to the reactor, and the reactor temperature was raised to 40°C. After the reaction started, vinylidene fluoride monomer was continuously added to maintain the system pressure at 7 MPa. After 1.5 h of reaction, the reactor temperature was raised to 60 ℃ reaction, the remaining initiator diethylhexyl peroxydicarbonate 1.2g was added into the reactor three times (20min interval), and vinylidene fluoride monomer was continuously added to maintain the system pressure at 12MPa. After the reaction, the unreacted vinylidene fluoride monomer was removed, and the slurry product was transferred to a receiving tank through a lower expansion valve. After filtering the mother liquor, 15L of ultrapure water was added to the filter cake, and the mixture was stirred evenly and then filter pressed. The product was then washed with sulfuric acid (0.569g) / water (5L). After continuous stirring and dispersing washing for 30min, the above washing operation was performed with pure water until the final filtrate conductivity was less than 2μS / cm, and the sample was then dried at 80℃ for 10h.
[0068] Example 3
[0069] In a 5-liter autoclave, 2400 g of ultrapure water, a pre-prepared nano zinc oxide (7.5 g) / water (420 g) dispersion, 1.5 g of diethylhexyl peroxydicarbonate initiator, 45 g of ethyl acetate chain transfer agent, and 4.5 g of polyethylene glycol dispersant were added. Nitrogen was introduced into the system under negative pressure for 5 times to control the oxygen content of the system below 20 ppm. Then, the stirring speed was set to 650 rpm, 1500 g of vinylidene fluoride monomer was added to the reactor, and the reactor temperature was raised to 50°C. After the reaction started, vinylidene fluoride monomer was continuously added to maintain the system pressure at 8 MPa. After 1.5 h of reaction, the reactor temperature was raised to 75 ℃ reaction, the remaining initiator diethylhexyl peroxydicarbonate 6g was added into the reactor three times (20min interval), and vinylidene fluoride monomer was continuously added to maintain the system pressure at 14MPa. After the reaction, the unreacted vinylidene fluoride monomer was removed, and the slurry product was transferred to a receiving tank through the lower expansion valve. After filtering the mother liquor, 15L of ultrapure water was added to the filter cake, and the mixture was stirred evenly and then filter pressed. The product was then washed with sulfuric acid (13.5g) / water (10L). After continuous stirring and dispersing washing for 30min, the above washing operation was performed with pure water until the final filtrate conductivity was less than 2μS / cm, and the sample was then dried at 80℃ for 10h.
[0070] Example 4
[0071] In a 5-liter autoclave, 1950 g of ultrapure water, a pre-prepared nano-magnesium oxide (1.5 g) / water (90 g) dispersion, 0.6 g of diethylhexyl peroxydicarbonate initiator, 30 g of ethyl acetate chain transfer agent, and 0.5 g of polyethylene glycol dispersant were added. Nitrogen was introduced into the system under negative pressure for 5 times to control the oxygen content of the system below 20 ppm. Then, the stirring speed was set to 600 rpm, 1500 g of vinylidene fluoride monomer was added to the reactor, and the reactor temperature was raised to 44°C. After the reaction started, vinylidene fluoride monomer was continuously added to maintain the system pressure at 7.5 MPa. After 1.5 h of reaction, the reactor temperature was raised to 70°C for reaction. The remaining initiator diethylhexyl peroxydicarbonate (2.4 g) was added into the reactor three times (with an interval of 20 min), and vinylidene fluoride monomer was continuously added to maintain the system pressure at 12.5 MPa. After the reaction, the unreacted vinylidene fluoride monomer was removed, and the slurry product was transferred to a receiving tank through the lower expansion valve. After filtering the mother liquor, 15 L of ultrapure water was added to the filter cake, and the mixture was stirred evenly and then filtered. The product was then washed with sulfuric acid (1.987 g) / water (5 L). After continuous stirring and dispersing washing for 30 min, the above washing operation was performed with pure water until the final filtrate conductivity was less than 2 μS / cm. The sample was then dried at 80°C for 10 h.
[0072] Example 5
[0073] In a 5-liter autoclave, 1950 g of ultrapure water, a pre-prepared nano-alumina (1.5 g) / water (90 g) dispersion, 0.6 g of diethylhexyl peroxydicarbonate initiator, 30 g of ethyl acetate chain transfer agent, and 0.5 g of polyethylene glycol dispersant were added. Nitrogen was introduced into the system under negative pressure for 5 times to control the oxygen content of the system below 20 ppm. Then, the stirring speed was set to 600 rpm, 1500 g of vinylidene fluoride monomer was added to the reactor, and the temperature of the reactor was raised to 44°C. After the reaction started, vinylidene fluoride monomer was continuously added to maintain the system pressure at 7.5 MPa. After 1.5 h of reaction, the temperature of the reactor was raised to 70°C for reaction. The remaining initiator diethylhexyl peroxydicarbonate (2.4 g) was added into the reactor three times (with an interval of 20 min), and vinylidene fluoride monomer was continuously added to maintain the system pressure at 12.5 MPa. After the reaction, the unreacted vinylidene fluoride monomer was removed, and the slurry product was transferred to a receiving tank through the lower expansion valve. After filtering the mother liquor, 15 L of ultrapure water was added to the filter cake, and the mixture was stirred evenly and then filtered. The product was then washed with sulfuric acid (1.987 g) / water (5 L). After continuous stirring and dispersing washing for 30 min, the above washing operation was performed with pure water until the final filtrate conductivity was less than 2 μS / cm. The sample was then dried at 80°C for 10 h.
[0074] Example 6
[0075] In a 5-liter autoclave, 1950 g of ultrapure water, a pre-prepared nano zinc oxide (1.5 g) / water (90 g) dispersion, 0.6 g of diethylhexyl peroxydicarbonate as initiator, 30 g of ethyl acetate as chain transfer agent, and 0.5 g of polyethylene glycol as dispersant were added. Nitrogen was introduced into the system under negative pressure for 5 times to control the oxygen content of the system below 20 ppm. Then, the stirring speed was set to 600 rpm, 1500 g of vinylidene fluoride monomer was added to the reactor, and the reactor temperature was raised to 70 ° C. After the reaction started, vinylidene fluoride monomer was continuously added to maintain the system pressure at 12. 5MPa, the remaining initiator diethylhexyl peroxydicarbonate 2.4g was added into the reactor three times (20min intervals), and the unreacted vinylidene fluoride monomer was removed after the reaction was completed. The slurry product was transferred to a receiving tank through the lower expansion valve, and the mother liquor was filtered. 15L of ultrapure water was added to the filter cake, and the mixture was stirred evenly and then filter pressed. The product was then washed with sulfuric acid (1.987g) / water (5L). After continuous stirring and dispersing washing for 30min, the above washing operation was performed with pure water until the final filtrate conductivity was less than 2μS / cm, and the sample was then dried at 80℃ for 10h.
[0076] Example 7
[0077] In Example 7, other conditions are the same as those in Example 1, except that zirconium oxide is used instead of nanoparticles.
[0078] Example 8
[0079] In Example 8, other conditions are the same as in Example 1, except that titanium dioxide is used instead of nanoparticles.
[0080] Example 9
[0081] In Example 9, other conditions are the same as those in Example 1, wherein zinc hydroxide is used instead of nanoparticles, the total amount of initiator added is adjusted to 0.3% of the mass of vinylidene fluoride (base amount), and the amount of hydroxyethyl methylcellulose used as the dispersant is adjusted to 0.1% of the mass of vinylidene fluoride (base amount).
[0082] Example 10
[0083] In Example 10, other conditions are the same as those in Example 1, wherein magnesium hydroxide is used instead of nanoparticles, the total amount of initiator added is adjusted to 0.3% of the mass of vinylidene fluoride (base amount), and the amount of hydroxyethyl methylcellulose used as the dispersant is adjusted to 0.1% of the mass of vinylidene fluoride (base amount).
[0084] Embodiment 11
[0085] In Example 11, other conditions are the same as those in Example 1, wherein aluminum hydroxide is used instead of nanoparticles, the total amount of initiator added is adjusted to 0.3% of the mass of vinylidene fluoride (base amount), and the amount of hydroxyethyl methylcellulose used as the dispersant is adjusted to 0.1% of the mass of vinylidene fluoride (base amount).
[0086] Comparative Example 1
[0087] In a 5-liter autoclave, 1950 g of ultrapure water, 0.6 g of initiator diethylhexyl peroxydicarbonate, 30 g of chain transfer agent ethyl acetate, and 0.5 g of dispersant polyethylene glycol were added. Nitrogen was introduced into the system under negative pressure for 5 times to control the oxygen content of the system below 20 ppm. Then, the stirring speed was set to 600 rpm, 1500 g of vinylidene fluoride monomer was added to the reactor, and the temperature of the reactor was raised to 44 ° C. After the reaction started, vinylidene fluoride monomer was continuously added to maintain the system pressure at 7.5 MPa. After 1.5 hours of reaction, the temperature of the reactor was raised to 70 ° C for reaction, and the remaining initiator dicarbonate was removed. 2.4 g of diethylhexyl acrylate was added to the reactor three times (20 min intervals), and vinylidene fluoride monomer was continuously added to maintain the system pressure at 12.5 MPa. After the reaction was completed, the unreacted vinylidene fluoride monomer was removed, and the slurry product was transferred to a receiving tank through the lower expansion valve. After filtering the mother liquor, 15 L of ultrapure water was added to the filter cake, and after stirring evenly, a filter press operation was performed. The product was then washed with sulfuric acid (1.987 g) / water (5 L). After continuous stirring and dispersing washing for 30 min, the above washing operation was performed using pure water until the final filtrate conductivity was less than 2 μS / cm, and the sample was then dried at 80°C for 10 h.
[0088] Comparative Example 2
[0089] In a 5-liter autoclave, 1950 g of ultrapure water, 0.6 g of initiator diethylhexyl peroxydicarbonate, 30 g of chain transfer agent ethyl acetate, and 0.5 g of dispersant polyethylene glycol were added. Nitrogen was introduced into the system under negative pressure for 5 times to control the oxygen content of the system below 20 ppm. Then, the stirring speed was set to 600 rpm, 1500 g of vinylidene fluoride monomer was added to the reactor, and the temperature of the reactor was raised to 70°C. After the reaction started, vinylidene fluoride monomer was continuously added to maintain the system pressure at 12.5 MPa. The remaining initiator peroxydicarbonate was replaced by nitrogen for 5 times. 2.4g of diethylhexyl dicarbonate was added to the reactor three times (20min intervals). After the reaction was completed, the unreacted vinylidene fluoride monomer was removed, and the slurry product was transferred to the receiving tank through the lower expansion valve. After filtering the mother liquor, 15L of ultrapure water was added to the filter cake, and the filter press was performed after stirring evenly. Then the product was washed with sulfuric acid (1.987g) / water (5L). After continuous stirring and dispersion washing for 30min, the above washing operation was performed with pure water until the final filtrate conductivity was less than 2μS / cm, and then the sample was dried at 80℃ for 10h. The sample test results are as follows:
[0090] Table 1 Properties of polyvinylidene fluoride resin
[0091]
[0092]
[0093] It can be seen from the table that the polyvinylidene fluoride resin synthesized by the method of the present invention has a higher crystallinity than that synthesized by a conventional polymerization method, and the β-crystalline phase accounts for most of the crystalline phase, and the molecular weight distribution is also narrow, which has potential application prospects in the field of piezoelectric polymers.
[0094] The above embodiments are merely examples for the purpose of clear explanation and do not mean that the present invention is limited thereto. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. However, the obvious changes or modifications derived therefrom are still within the protection scope of the present invention.
Claims
1. A method for preparing a polyvinylidene fluoride resin, characterized in that: The following steps are involved: (1) adding water, chain transfer agent, initiator, nanoparticles and dispersant into a reaction kettle; (2) adding vinylidene fluoride monomer as a base under stirring conditions, and then performing a polymerization reaction; (3) After the polymerization is completed, unreacted monomers are removed and post-processed to obtain polyvinylidene fluoride resin.
2. The preparation method according to claim 1, characterized in that: The resistivity of the water in step (1) is greater than 18.3 MΩ·cm at 25° C.; Preferably, the amount of water added in step (1) is 100%-160% of the mass of the vinylidene fluoride monomer used as the base, preferably 110-150%; Preferably, the chain transfer agent in step (1) is an ester, preferably a carboxylate or a carbonate, more preferably one or more of ethyl acetate, dipropyl malonate, diethyl succinate, dipropyl succinate, diethyl malonate, diisopropyl carbonate, dimethyl carbonate, diethyl carbonate, and vinyl carbonate. More preferably, the amount of the chain transfer agent added is 0.3 to 3 wt% of the mass of the vinylidene fluoride monomer used as the base.
3. The preparation method according to claim 1 or 2, characterized in that: The nanoparticles are nano metal / non-metal oxides or hydroxides; Preferably, the nano metal oxide or hydroxide is preferably an alkaline earth metal or transition metal oxide or hydroxide, more preferably an oxide or hydroxide of metal zinc, aluminum, magnesium, titanium, or zirconium; Preferably, the nanoparticles include but are not limited to one or a combination of two or more of nano zinc oxide, nano aluminum oxide, nano magnesium oxide, nano zinc hydroxide, nano aluminum hydroxide, nano magnesium hydroxide, nano titanium oxide, nano zirconium oxide; Preferably, the nanoparticles have a particle size of 10-500 nm, preferably 10-100 nm; Preferably, the amount of the nanoparticles used is 0.03-0.5% of the mass of the vinylidene fluoride monomer used as the base.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The dispersant in step (1) is one or a combination of two or more of polyethylene glycol, methyl cellulose, ethyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, and hydroxyethyl methyl cellulose; Preferably, the amount of the dispersant is 0.01 to 0.3% of the mass of the vinylidene fluoride monomer used as the base; Preferably, after adding the bottom raw material to the polymerization reactor, an oxygen removal operation is required, and multiple nitrogen replacements are performed under a negative pressure environment to deoxygenate the final oxygen content, and the final oxygen content is controlled below 20 ppm.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The reactor is a high-pressure vertical reactor or a high-pressure spherical reactor. The length-to-diameter ratio of the reactor should be less than 1.5, the ratio of the blade diameter to the inner diameter of the reactor should be greater than 0.5, and the speed of the reaction process is 450rpm-650rpm; Preferably, the polymerization reaction temperature is 40-75°C and the pressure is 7-14Mpa.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The polymerization reaction is carried out in two stages; Preferably, the temperature of the first stage of suspension polymerization is 40-50°C, and the temperature of the second stage is 60-75°C; Preferably, the reaction pressure is controlled by the amount of vinylidene fluoride introduced during the reaction. The vinylidene fluoride monomer is fed continuously. Before the reaction starts, vinylidene fluoride is first introduced as a bottom layer. During the reaction, vinylidene fluoride monomer is continuously introduced into the system, and the reaction pressure is maintained at 7-14Mpa.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The initiator is a peroxide initiator or an azo initiator, preferably one or more of dibenzoyl peroxide, dilauroyl peroxide, azobisisobutyronitrile, azobisisoheptanenitrile, tert-butyl peroxyisopropyl formate, and diethylhexyl peroxydicarbonate; Preferably, the amount of the initiator added is 0.1-0.5wt% of the mass of the vinylidene fluoride monomer used as the base; Preferably, the initiator is added in multiple portions.
8. The preparation method according to any one of claims 1 to 6, characterized in that: The post-treatment after the reaction includes mother liquor slurry filtration, acid washing, pure water washing, filter pressing, and drying; Preferably, after the mother liquor slurry is filtered, water is added to the filtered filter cake for stirring and dispersion, and the amount of water added is 5-20 times the weight of the wet material, preferably 10 times, and then the slurry is pressed, wherein most of the nanoparticles can be removed, and then the material is stirred and washed with an acid solution for at least 30 minutes, and after the acid washing, it is continued to be washed and filtered with water until the conductivity of the filtrate is less than 2 μS / cm; Preferably, the type of acid used for washing includes but is not limited to one or more of sulfuric acid, hydrochloric acid, nitric acid, and acetic acid, and the amount of acid added is 105-150 mol % of the nanoparticles.
9. Use of the polyvinylidene fluoride resin prepared by the preparation method according to any one of claims 1 to 8 for piezoelectric materials.
Citation Information
Patent Citations
Method of continuous preparation of PVDF film with high beta-crystal content through melt extrusion-rolling
CN109762188A
Preparation method of high-crystallinity beta-PVDF (Polyvinylidene Fluoride)
CN117229526A
Preparation method for beta crystal profax resin
CN101429259A
Method for preparing Beta-crystalline polypropylene
CN101768230A
Preparation method for high heat resistance polyvinylidene fluoride
CN102336854A